THE EFFECT OF MUROTTAL ALQURAN THERAPHY TOWARDS HEMODYNAMIC STATUS OF PATIENTS WITH DECREASING CONSCIOUSNESS IN THE ICU OF SAMPANG - Henny Ekawati (NHM PRESS, 1970)
patient with decreasing of consciousness isa condition it has been the patient wereable to give a normal response to stimuli.From field data, obtained there still manypatients with decreasing of consciousnesswhere their hemodynamic status isunstable. Thus, it is necessary to control theimpact of decreasing of consciousness inthe form of hemodynamic instability byusing Al-Quran murottal therapy. Thisstudy aimed to analyze the effect of AlQuran mutottal therapy towardshemodynamic status in patients withdecreasing of consciousness.This study used Quasy-Experimentaldesign. The instrument of this study isobservation sheet. Most of the population ispatient with decreasing of consciousness asmuch as 18 respondents. Researcher usedpurposive sampling techniques and decidednine groups as experimental group weregiven treatment. The treatment is Al-Quranmurottal therapy which was given for 3days and 9 groups as control group whichwas not given Al-Quran murottal therapy.Based on research results using statisticaltest of independent t- test showed that TDsystole ρvalue = 0.006, TD diastole ρvalue= 0.004, RR ρvalue = 0.007 and HR ρvalue= 0.014, overall value ρvalue <α = 0.05, soHo rejected. It means that there is notherapeutic effect Al-Quran murottaltherapy towards hemodynamic status inpatients with decreasing of consciousness.From the result of this study, the researcherexpecte this Al-Quran murottal therapy canbe used for alternative therapy for patientswith decreasing of consciousness that theirhemodynamic status is stable.